A STATISTICAL STUDY OF THE USE OF THE INTERNET BY THE POPULATION IN THE RUSSIAN FEDERATION - E. Dolgikh; L. Parshintseva (Вестник университета)
The main results of surveys of the population of the Russian Federation on the use of information technologies and information and telecommunication networks for the period from 2014 to 2016 have been described. An analysis of the population’s use of the Internet, including in terms of gender, age, place of residence has been made. Particular attention has been paid to the study of the use of the Internet for the purchase, ordering of goods and services. The article characterizes the most popular goods and services ordered by the population via the Internet. The use of the Internet for the purpose of interaction with public authorities and local self-government has been considered. This paper pays attention to using by our population of the Single portal of public services of the Russian Federation.